Editorial of Special Issue "Hyaluronic Acid in Human Medicine" - Suchánek, Jakub (Biomolecules, 2022)
Hyaluronic acid (HA) is an acidic, non-sulfated glycosaminoglycan that is intensively studied as a biodegradable and biocompatible material for scaffolding, regenerative medicine, and clinical applications [...].
Keywords: Hyaluronic Acid; Regenerative Medicine; Biocompatible Materials; lidé; biokompatibilní materiály; kyselina hyaluronová; regenerativní lékařství; Humans